Genetic resources of neotropical fishes - Hilsdorf, Alexandre W. S.; Hallerman, Eric M. (Springer, 2017)
The aim of this book is to systematize and discuss population genetic studies of freshwater fish in a region that harbors the greatest diversity of species among all inland water ecosystems. This volume explores the genetic evaluation for a number of orders, families and species of Neotropical fishes, and provides an overview on genetic resources and diversity and their relationships with fish domestication, breeding, and food production.
Keywords: Fishes -- Latin America -- Genetics.; Latin America.; elektronické knihy; electronic books